Novel Fluorescent Dyes for Single DNA Molecule Techniques - Alexander Zarkov; Aleksey Vasilev; Todor Deligeorgiev; Stoyno Stoynov; Marina Nedelcheva-Veleva (Molecular Imaging)
To answer the demands of scientific and medical imaging issues, the family of nucleic acid fluorescent dyes is constantly enlarging. Most of the developed dyes reveal high qualities in bulk solution assays but are inefficient to produce a strong and sufficiently stable signal to enable the application of single-molecule techniques. Therefore, we tested 12 novel monomeric and homodimeric cyanine dyes for potential single DNA molecule imaging. Although their qualities in bulk solutions have already been described, nothing was known about their behavior on a single-molecule level. All 12 dyes demonstrated strong emission when intercalated into single DNA molecules and stretched on a silanized surface, which makes them the perfect choice for fluorescent microscopy imaging. A comparison of their fluorescence intensity and photostability with the most applicable dyes in single-molecule techniques, fluorescent dyes YOYO-1 and POPO-3, was carried out. They all exhibited a strong signal, comparable to that of YOYO-1. However, in contrast to YOYO-1, which is visualized under a green filter only, their emission permits red filter visualization. As their photostability highly exceeds that of similar spectrum POPO-3 dye, the studied dyes stand out as the best choice for a broad range of solid surface single-molecule applications when yellow to red DNA backbone fluorescence is needed.